1996
DOI: 10.1002/j.2048-7940.1996.tb01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Type A: Hostility and Coronary Heart Disease—Implications for Research and Practice

Abstract: Research into the psychological and behavioral correlates of coronary heart disease (CHD) has gone beyond the traditional description of the Type A behavior pattern and is focusing instead on components that may be more sensitive predictors of CHD endpoints. One component being investigated frequently is hostility. Many questions related to hostility and CHD remain unanswered and warrant further research. Implications for practice include a need for reexamination of standard risk reduction programs in light of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Anger and hostility are two important dimensions in the context of personality attributes and have been associated with several personality traits or types. Many studies have found that the hostility and anger components of the type A behavior pattern are more sensitive predictors of CVDs 6, 7, 18. Furthermore, a meta-analysis of 25 studies and 19 studies separately which investigated the coronary heart disease (CHD) outcome in healthy populations and those with preexisting CHD revealed that both anger and hostility were significantly associated with increased CHD events both in healthy population studies (hazard ratio [HR] −1.19; p = 0.008) and those with previous CHD population studies (HR, −1.24; p = 0.002) 6 .…”
Section: Evolution Of the Conceptmentioning
confidence: 99%
“…Anger and hostility are two important dimensions in the context of personality attributes and have been associated with several personality traits or types. Many studies have found that the hostility and anger components of the type A behavior pattern are more sensitive predictors of CVDs 6, 7, 18. Furthermore, a meta-analysis of 25 studies and 19 studies separately which investigated the coronary heart disease (CHD) outcome in healthy populations and those with preexisting CHD revealed that both anger and hostility were significantly associated with increased CHD events both in healthy population studies (hazard ratio [HR] −1.19; p = 0.008) and those with previous CHD population studies (HR, −1.24; p = 0.002) 6 .…”
Section: Evolution Of the Conceptmentioning
confidence: 99%
“…Hostility is one component of TABP that has been identified as highly associated with cardiac morbidity and mortality. 37,38 Our current TABP scale does not include hostility items, and it is possible that had we used a scale that included such items, different outcomes would have been found. This study may be limited in its findings because of the population of older minority women.…”
Section: Discussionmentioning
confidence: 99%